Association between adolescent obesity and early adulthood healthcare utilization—a two-cohort prospective study - Emilia Hagman; Vidar Halsteinli; Resthie R. Putri; Christina Hansen Edwards; Gudrun Waaler Bjørnelv; Claude Marcus; Rønnaug A. Ødegård (BMC Medicine, 2025)
Abstract Background Pediatric obesity is a growing global health challenge, with long-term implications for individuals and healthcare systems. Existing studies on the association between pediatric obesity and healthcare use in adulthood are limited and often rely on mathematical simulation models. This study aims to provide real-world data on the impact of adolescent obesity on specialized healthcare utilization and costs in early adulthood. Methods This study analyzed data from two longitudinal cohorts: a population-based cohort from Norway (Young-HUNT) and a clinical cohort from Sweden (BORIS), the latter with matched general population comparators. Individuals included were born between 1987 and 1994, with BMI measurements at ages 13–19, and follow-up data from ages 20 to 30 years. Healthcare utilization and costs were assessed using national patient registries. Results A total of 7592 individuals from Norway (5.7% with adolescent obesity) and 1543 individuals from Sweden with adolescent obesity, accompanied with 7330 matched general population comparators, were included. Among females, adolescent obesity was associated with significantly higher specialized healthcare utilization and costs in young adulthood, e.g., in Sweden, females with adolescent obesity had a 57% probability of annual specialized healthcare visits at ages 25–29, compared to 49% among the general population, p < 0.0001. In Norway, a similar pattern was observed. Among males, the association between obesity and healthcare utilization/annual specialized visits was less prominent. Annual excess costs for females with a history of adolescent obesity ranged from €578 to €835, while males showed minimal or no annual excess costs. Conclusions Analyses of real-world data cohorts from Norway and Sweden reveal that adolescent obesity is associated with increased healthcare utilization and costs in young adulthood, exceeding previous estimates. A distinct sex difference was evident, with females incurring higher costs compared to males.